Temperature Boundary Condition Models for Concrete Bridge Members - Riding, Kyle A.; Poole, Jonathan L.; Schindler, Anton K.; Juenger, Maria C. G.; Folliard, Kevin J. (My University, 2010)
The temperature development of mass concrete elements is strongly dependent on constituent materials and mixture proportions, as well as the formwork type, geometry, and environmental conditions. This paper presents a method to account for the effects of convection, radiation, and shading on the surface temperature of mass concrete. Solar radiation, atmospheric radiation, surface-emitted radiation, and formwork radiation exchange were considered. Wind speed, ambient temperature, and surface roughness were included in the convection model. The model described was incorporated into a mass concrete temperature prediction model. The predicted temperatures were then compared with measured near-surface concrete temperatures. The ability of the model to predict the maximum temperature and maximum temperature difference were also examined. The results show that the model accurately estimates the near-surface concrete temperatures, the maximum temperature, and maximum temperature difference of the 12 concrete members instrumented.
Keywords: Formword; Mass concrete; Temperature prediction